Two new combinations of Middletonia (Gesneriaceae) in China - Qi-Yang Li; Xin-Xiang Bai; Song-Tao He (PhytoKeys)
In 2016, systematic studies of the tribe Loxocarpinae A.DC. supported the establishment of the new genus Middletonia C. Puglisi. This study was based on inference and parsimony analyses of a phylogenetic tree derived from the nuclear ITS and plastid trnL-trnF regions, constructing the most recent phylogeny that includes the genera Middletonia and Paraboea. The results showed that the current generic delimitation within the tribe differs from the clades delineated by phylogenetic analysis, and both morphological and molecular evidence support treating the Hainan endemics Paraboea changjiangensis Xing & Z.X.Li and P. hainanensis (Chun) Burtt as species of Middletonia. Therefore, this paper re-delimits the genera Middletonia and Paraboea, aiming to establish a more natural classification, and proposes the new combinations Middletonia changjiangensis (F.W.Xing & Z.X.Li) X.X.Bai, comb. nov., and Middletonia hainanensis (Chun) X.X.Bai, comb. nov., providing a valuable framework for the development and comparative studies of the molecular systematics of the family Gesneriaceae.